An Investigation on the Influence of Brand-related Apps on Brand Engagement of Green Brand and Following Behaviours - HUANG, YUN-TING (2016)
There is a significant growth of the number of smartphone applications’ users around the world. Moreover, the usage of apps dominates the time spent with mobile (Chaffey, 2016). A clear business opportunity via mobile applications is appeared. Therefore, this research aims to discuss the influence of the features of brand-related applications (apps) on brand engagement and the consequences of brand engagement. The brand used as an example in this study is set as the Taiwanese green brand, Gogoro. The designed questionnaire was distributed through online platform. The further analysis for the data was conducted through IBM SPSS 23 software. The results support the hypotheses that the three features of brand-related apps positively influence on brand engagement, perceived value and satisfaction. Moreover, brand engagement significantly influences brand attitude and (e)-word-of-mouth. However, some of the features do not have the significant influence. The limitations and recommendations for further research are also included in the end.